GeoGebra Integration in Mathematics Teaching: Bridging Research and Classroom Practice - Ardina, Genaro; Bautista, Guillermo; delos Santos, Maria Salud (Journal of Interdisciplinary Perspectives, 2025)
The integration of technology in mathematics education offers dynamic tools for enhancing students’ Mathematics engagement, motivation, and understanding. This study assessed and explored the practical application of GeoGebra, a dynamic mathematics software, to translate research findings into actual classroom practices within a teacher education context. Using a mixed-method sequential explanatory design, the study developed and implemented nine structured GeoGebra-integrated lesson plans guided by Madeline Hunter’s Instructional Model. The participants were Bachelor of Secondary Education students majoring in Mathematics from a private university in Cebu province. Quantitative data on students’ mathematics motivation, engagement, and understanding were collected using validated instruments, followed by qualitative analysis of students’ perceptions and experiences. Results showed numerical improvements across all domains, with post-test findings indicating higher levels of Mathematics motivation, engagement, and understanding. However, statistical tests revealed no significant differences between pre- and post-test scores, although significant positive correlations were found among the three constructs. Thematic analysis highlighted benefits such as improved visualization and deeper understanding, alongside challenges including limited access to devices, unstable internet connections, and initial difficulties in using GeoGebra. Despite these constraints, students appreciated the creative possibilities offered by GeoGebra and its ability to connect mathematical concepts to real-world applications. The study culminated in the development of a compendium of lesson plans designed to support educators in effectively integrating GeoGebra into their instruction. These findings highlight the potential of structured technology integration in developing student-centered and interactive mathematics learning environments, while also underscoring the need for adequate pedagogical support for successful implementation.